2019
DOI: 10.5694/mja2.12102
|View full text |Cite
|
Sign up to set email alerts
|

The Australasian Society of Clinical Immunology and Allergy infant feeding for allergy prevention guidelines

Abstract: Introduction The Australasian Society of Clinical Immunology and Allergy, the peak professional body for clinical immunology and allergy in Australia and New Zealand, develops and provides information on a wide range of immune‐mediated disorders, including advice about infant feeding and allergy prevention for health professionals and families. Guidelines for infant feeding and early onset allergy prevention were published in 2016, with additional guidance published in 2017 and 2018, based on emerging evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 35 publications
2
95
1
1
Order By: Relevance
“…We found that most parents (86%) reported that their infants had eaten peanut before 12 months of age, consistent with current ASCIA guidelines . This proportion is much higher than the estimate of 30.2% determined by an Australian population survey undertaken between 2009 and 2011, and follows major efforts to promote the revised ASCIA guidelines in both the medical and general media.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found that most parents (86%) reported that their infants had eaten peanut before 12 months of age, consistent with current ASCIA guidelines . This proportion is much higher than the estimate of 30.2% determined by an Australian population survey undertaken between 2009 and 2011, and follows major efforts to promote the revised ASCIA guidelines in both the medical and general media.…”
Section: Discussionsupporting
confidence: 68%
“…The prevalence of early childhood food allergy in Australia is among the highest in the world . To reduce the incidence of food allergies, the Australasian Society of Clinical Immunology and Allergy (ASCIA) recently revised their guidelines for infant feeding and allergy prevention, recommending that common food allergens, including peanut and egg, be introduced during the first year of life . These guidelines, underpinned by evidence from randomised controlled trials, contrast with earlier recommendations, including advice by the National Health and Medical Research Council, to avoid some allergenic foods during early childhood.…”
mentioning
confidence: 99%
“…While this provides a suitable source of commercial food options for infants with existing food allergy, these products do not reflect contemporary infant feeding and allergy prevention guidelines, which encourage deliberate regular inclusion of common food allergen-containing foods in the diet during infancy. [6][7][8][9] This is especially important for the introduction of peanut and eggcontaining foods, which were the allergens focused on in randomised controlled trials, [1][2][3][4] which have provided level 1 evidence for the recent infant feeding and allergy prevention guideline updates. In Australia, early regular introduction of egg and peanut in infant diets is especially critical given the findings from the large cohort study where egg and peanut food allergies were identified to affect 1 in every 10 infants.…”
Section: Discussionmentioning
confidence: 99%
“…21 In Australia, this has been addressed by the development of evidence-based consensus wording for infant feeding guidelines for allergy prevention, 8 adopted by the Australasian Society of Clinical Immunology and Allergy. 9 The Australasian Society of Clinical Immunology and Allergy has also published practical infant feeding advice for parents, 22 and the Australian federally funded National Allergy Strategy 'Nip Allergies in the Bub' program 23 has used a public health approach to promote the change in feeding guidelines to reduce the risk of food allergy, including practical information for parents about how to include common allergens (particularly peanut and egg) in infant diets using home-prepared food options. Given the insufficient quantities of many food allergens in commercial infant foods in Australia that we have identified during this audit, clear messaging of the use of home-prepared foods including the major food allergens requires ongoing public health messaging approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation